DEVELOPMENT AND VALIDATION OF A LEADERSHIP TRAINING PROGRAM FOR NURSES - Martins,Beatriz Gonçalves (2019)
ABSTRACT Objectives: To identify strategies that facilitate the development of leadership, correlating them with characterization of variables, and to create and validate a leadership training program for nurses. Method: developed in two phases. First: a cross-sectional study, performed in a general hospital in São Paulo, Brazil. The 70 nurses in the sample had at least three months of work experience in the institution. An instrument was used to collect data with characterization variables (gender, age, postgraduate, work shift and length of working career and contact with the theme of leadership) and collection of suggested strategies to develop more prominent leadership in the literature. Data were collected (February-April 2016) and analyzed descriptively. The Mann-Whitney and Kruskal Wallis tests were used to verify the correlations (p<0.05). Second phase: validation study of the program using the Delphi technique, from March to June 2017. Following the construction of the program, and considering the results obtained in the first phase, judges were selected with the following criteria: to be a nurse, researcher in leadership and nursing administration, with article publications in the last five years and teaching experience. Results: the strategies indicated in the first phase were: performance of experienced leaders as facilitators in the teaching-learning process (the highest scores were given by men; p=0.033) and establishment of partnerships between university and hospital (the largest choice was made by young nurses, p=0.019). In the second phase, a content validity index of 0.81 was reached, considered satisfactory. Conclusion: the program can be applied, and future studies will evaluate its effectiveness.